Abernethy malformation: a case report - Pathak Ashish; Agarwal Nitin; Mandliya Jagdish; Gehlot Prateek; Dhaneria Mamta (BMC, 2012)
Abstract Background Abernethy malformation is a very rare congenital vascular malformation defined by diversion of portal blood away from liver. It is commonly associated with multiple congenital anomalies. We present a case of Abernethy malformation, without associated congenital anomalies from India. Case presentation A 5-year-old female child presented with short history of jaundice. A provisional diagnosis of acute viral hepatitis was made in view of clinical presentation and local endemicity of viral hepatitis A. Persistence of jaundice on follow up after 4 weeks led to detailed investigations. Ultrasound and doppler study of abdomen revealed drainage of portal vein into inferior vena cava. CT angiography was performed which confirmed the diagnosis of Type 1 b Abernethy malformation without associated major anomalies. We discuss the common clinical presentations, associated anomalies, diagnostic workup and treatment options of this disorder. Conclusion The treatment of the patients with congenital porto-systemic shunts depends on the site of the shunt, associated congenital anomalies and the extent of liver damage but the prognosis depends on the complications irrespective of anatomical type. However, the extent of associated abnormalities should not deter paediatricians to refer patients for treatment. Whenever possible closure of the shunt should be advised for cure or to prevent complications. Only symptomatic type I patients with absence of possibility to close the shunt may require liver transplant. Long-term follow-up is indicated for all patients.